KESENJANGAN PENDIDIKAN ANTARA WILAYAH PERKOTAAN DAN PEDESAAN DI INDONESIA: KAJIAN LITERATUR REVIEW TERHADAP FAKTOR, DAMPAK, DAN UPAYA PENANGANAN - Sucipto, Adi; Umami, Nailariza; Agatha Sri Widyanti Hastuti, Maria (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The education gap between urban and rural areas in Indonesia remains a complex and ongoing problem. Differences in access to infrastructure, socioeconomic conditions, the quality of teaching staff, and technological developments contribute to disparities in educational quality and opportunities. This study aims to comprehensively examine the causes, impacts, and efforts to address the education gap through a literature review approach. The method used is a literature study with a descriptive qualitative approach, where data is obtained from various relevant scientific articles and analyzed using thematic analysis techniques. The results of the study indicate that the education gap is influenced by key factors such as limited infrastructure, socioeconomic inequality, uneven distribution of teaching staff, and the gap in digital access. The resulting impacts are not only in the quality of learning and student learning outcomes, but also have implications for the low development of individual potential, increasing social inequality, and hampered economic growth. Various government efforts such as educational assistance programs, equal distribution of teaching staff, and digitalization of learning have been implemented, but their implementation still faces obstacles in terms of equity, suitability to local conditions, and effectiveness. Therefore, a more integrated and adaptive approach is needed to reduce the education gap between rural and urban areas in Indonesia